2001
DOI: 10.1083/jcb.200105017
|View full text |Cite
|
Sign up to set email alerts
|

EGF-R signaling through Fyn kinase disrupts the function of integrin α6β4 at hemidesmosomes

Abstract: We have examined the mechanism and functional significance of hemidesmosome disassembly during normal epithelial cell migration and squamous carcinoma invasion. Our findings indicate that a fraction of EGF receptor (EGF-R) combines with the hemidesmosomal integrin α6β4 in both normal and neoplastic keratinocytes. Activation of the EGF-R causes tyrosine phosphorylation of the β4 cytoplasmic domain and disruption of hemidesmosomes. The Src family kinase inhibitors PP1 and PP2 prevent tyrosine phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
260
6
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(280 citation statements)
references
References 62 publications
12
260
6
2
Order By: Relevance
“…31 Previously, Fyn was shown to be required for the regulation of the b4 integrin and maintenance of hemidesmosomes, structures vital for epithelial integrity. 32 Blocking the P2X7 activity with oxATP To better understand these results and further investigate the role of P2X7 in promoting cell migration at the leading edge, we examined actin cytoskeletal rearrangements and focal adhesion dynamics in live cells. A marked decrease in membrane ruffling and minimal extension of lamellipodia at the leading edge were observed in oxATP-treated cells.…”
Section: P2x7 and Cell Migrationmentioning
confidence: 99%
“…31 Previously, Fyn was shown to be required for the regulation of the b4 integrin and maintenance of hemidesmosomes, structures vital for epithelial integrity. 32 Blocking the P2X7 activity with oxATP To better understand these results and further investigate the role of P2X7 in promoting cell migration at the leading edge, we examined actin cytoskeletal rearrangements and focal adhesion dynamics in live cells. A marked decrease in membrane ruffling and minimal extension of lamellipodia at the leading edge were observed in oxATP-treated cells.…”
Section: P2x7 and Cell Migrationmentioning
confidence: 99%
“…On the other hand, a number of reports have revealed that ITGB4 combines with several oncogenic receptor tyrosine kinases, including c-Met, ErbB1, and ErbB2, to amplify the signaling pathways that accelerate cancer invasion. [30][31][32] Because these growth factor receptors are overexpressed in a large number of patients with pancreatic cancers and are involved in cancer progression, 33,34 upregulated ITGB4 may associate with some of these overactive receptor tyrosine kinases, such as EGFR and c-Met, which are well-known EMT inducers, thereby promoting tumor invasion and EMT in pancreatic cancer.…”
Section: Knockdown Of Itgb4 Decreases Cell Motility In Pda Cellsmentioning
confidence: 99%
“…Although internalization by endocytosis has been assumed to be a mechanism to attenuate the signaling in response to the growth factor, increasing evidence demonstrates that a correct endocytotic pathway is important for EGFR signaling by controlling the specificity of the response. 36,37 Several studies have shown that internalized EGFR are enzymatically active, are still phosphorylated and maintain association with many adaptor proteins. [43][44][45] In addition, it has been recently shown that interaction with some adaptor proteins, such as eps8, a protein involved in cytoskeletal reorganization and actin remodeling, 46 occurs only at endosomal level.…”
Section: Egfr Internalization Is Altered In Pc3-ar Cellsmentioning
confidence: 99%